Sociální sítě jako zdroj symbolického kapitálu - Latislavová, Aneta (Univerzita Karlova, Fakulta sociálních věd, 2024)
This study focuses on identifying users' motivations for using social media platforms and the question of perceiving their activity as a source of symbolic capital. The paper also provides insights into individuals' behaviors on social networks and their perspectives on associated phenomena. The empirical part is conducted through mixed research methods, wherein phenomena are examined in detail through interviews followed by a questionnaire survey. The study identifies key factors for user motivation and activity and explores how users explain them. It analyzes the mutual social interaction among users and its importance for both online and offline communication. The study includes mapping the influence of influencers on their followers and the perceived positive and negative aspects of their activities. The research also investigates how respondents react to interruptions in online communication and the impact on their mental health. Tato studie se zaměřuje na identifikaci motivací uživatelů pro používání platforem sociálních sítí a otázku vnímání jejich aktivity jako zdroje symbolického kapitálu. Práce také nabízí pohled na chování jedinců na sociálních sítích a názory na fenomény s nimi spojenými. Empirická část je provedena formou smíšeného výzkumu, ve kterém jsou jevy detailněji zkoumány pomocí rozhovoru a následně dotazníkovým šetřením. Práce identifikuje klíčové faktory pro motivaci a aktivitu uživatelů a sleduje a jak si je sami vysvětlují. Analyzuje vzájemnou sociální interakci mezi uživateli a její důležitost pro online i off-line komunikaci. Součástí studie je i mapování vlivu influencerů na jejich sledovatele a vnímané pozitivních a negativních aspektů jejich aktivity. Práce se zaměřila také na to, jak respondenti reagují na přerušení online komunikace a jaké dopady to má na jejich duševní zdraví. Department of Sociology Katedra sociologie Faculty of Social Sciences Fakulta sociálních věd